Training Activities Through Waste Management Educational Seminars - Galih Abdul Fatah Maulani; Sopa Siti Marwah; Rubi Ana Syakinah; Ade Riska Nuraeni; Rizkil Mubarok; Fauzan Firdauh; Zidan Rafsanjani Zein (Indonesian Journal of Community Empowerment (IJCE), 2026)
Over time, plastic waste has become one of the most dangerous environmental pollutants because it is difficult to decompose and can even last for more than 1,000 years. The goal of this training is to provide a demonstration of technology that is easily applicable in everyday life, so that the community is better educated and motivated to actively participate. The training method is descriptive, targeting the village/sub-district community where the Community Service Program (KKN) is being implemented, particularly housewives, teenagers, and students who play an active role in household waste management habits. The training also opens up opportunities to utilize waste as a material with economic value. Inorganic waste such as plastic bottles, paper, and cans is starting to be viewed not only as waste but also as a resource that can be recycled into recycled products. Some participants are even interested in developing creative ideas, such as making crafts from used plastic or selling recyclable items to waste banks. Through appropriate education, it is hoped that the community will be able to manage waste safely and in accordance with health protocols.